Jahi McMath and the Ethics of the Brain Death Standard - Swazo, Norman K. (Bangladesh Journal of Bioethics, 2015)
How does one account for the discrepancy between the evidence of total and irreversible brain death and the current evidence of recovered brain function? This is the question that is raised by recent legal action in the case of 13-year old Jahi McMath, certified dead on the basis of neurological criteria but maintained in mechanical ventilation and medical/nursing care since then at the insistence of the parents who claim she is alive. In this brief discussion, the medical and legal issues are reviewed. Here the argument is advanced that this is not a case that means there should be a re-evaluation of the neurological criteria for determination of brain death. Instead, this case is to be understood as the exception that proves the rule. DOI: http://dx.doi.org/10.3329/bioethics.v5i3.21533 Bangladesh Journal of Bioethics 2014; 5(3):18-22